1028. Long-term Follow-up After a Switch to Bictegravir, Emtracitabine, Tenofovir Alafenamide from Dolutegravir, Abacavir, Lamivudine. (31st December 2020) - Brar, Indira; Ruane, Peter; Ward, Douglas; Molina, Jean-michel; Mills, Anthony; Berhe, Mezgebe; Brinson, Cynthia; Rampogal, Moti; Benson, Paul; Henry, Keith; Huang, Hailin; Andreatta, Kristen; et al.
Abstract: Background: Bictegravir, emtricitabine and tenofovir alafenamide (B/F/TAF) is a guidelines-recommended single-tablet regimen (STR) for people living with HIV-1 (PLWH). Week (W) 48 primary endpoint results of this phase 3 study switching to B/F/TAF from dolutegravir (DTG), abacavir (ABC) and lamivudine (3TC) established the safety and efficacy of B/F/TAF. Here we report outcomes from an open-label (OL) extension of B/F/TAF. Methods: Adults virologically suppressed on DTG, ABC, and 3TC were randomized 1:1 to switch to B/F/TAF once daily or continue their current regimen as a STR in a double blind (DB) manner. Unblinding occurred after the W48 primary endpoint, then participants received B/F/TAF in an OL extension while transitioning off the study. All participants who received B/F/TAF in the DB or OL phases are included in analyses. Efficacy was assessed as the proportion with HIV-1 RNA < 50 copies/mL at each study visit using missing=excluded (M=E) analysis, efficacy in in subgroups with pre-existing resistance was assessed using last observation carried forward. Safety was assessed by adverse events (AEs) and laboratory results. Results: 563 participants were randomized and treated (282 B/F/TAF, 281 ABC/DTG/3TC); 524 (93%) completed the DB phase and received OL B/F/TAF; a total of 547 participants received B/F/TAF in DB and/or OL phases: 11% women, 21% Black, median age 47 yrs (range 21, 71). The median duration of B/F/TAF was 96 weeks (IQR 49-119). HIV-1 RNA < 50 c/mL was maintained in 99-100% at all timepoints (M=E) through a maximum of 168 weeks, including high efficacy in those with archived resistance (Table 1). No participant developed resistance to B/F/TAF. Study drug-related AEs occurred in 7% on B/F/TAF; most were grade 1; the most common was headache (1.6%). 7 (1%) participants had an AE leading to premature study drug discontinuation, only 1, headache, occurred in the OL phase. Estimated GFR and lipids were mostly stable with slightly increased LDL at W96; weight changes are noted at W48 and W96. (Table 2). Table 1. Table 2. Conclusion: Extended follow-up to the study of switching to B/F/TAF from DTG/ABC/3TC, demonstrates continued high rates of virologic suppression with no resistance and excellent safety and tolerability of B/F/TAF through a maximum of 168 weeks for treatment of PLWH. Disclosures: Indira Brar, MD, Gilead (Speaker's Bureau)janssen (Speaker's Bureau)ViiV (Speaker's Bureau) Peter Ruane, MD, AbbVie (Consultant, Grant/Research Support, Speaker's Bureau)Bristol-Myers Squibb (Grant/Research Support)Gilead Sciences Inc. (Consultant, Grant/Research Support, Scientific Research Study Investigator, Shareholder, Speaker's Bureau)Idenix (Consultant)Janssen (Grant/Research Support, Speaker's Bureau)Viiv Healthcare (Grant/Research Support) Douglas Ward, MD, Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Merck (Advisor or Review Panel member)Viiv Healthcare (Advisor or Review Panel member, Speaker's Bureau) Jean-michel Molina, MD, PhD, Bristol-Myers Squibb (Advisor or Review Panel member)Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member)Janssen (Advisor or Review Panel member)Merck (Advisor or Review Panel member)Teva (Advisor or Review Panel member)Viiv Healthcare (Advisor or Review Panel member) Anthony Mills, MD, Gilead (Grant/Research Support, Advisor or Review Panel member)Janssen Pharmaceutica (Grant/Research Support, Advisor or Review Panel member)Merck (Grant/Research Support, Advisor or Review Panel member)Shionogi (Grant/Research Support)ViiV Healthcare (Grant/Research Support, Advisor or Review Panel member) Mezgebe Berhe, MD, Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator) Cynthia Brinson, MD, Gilead (Advisor or Review Panel member, Speaker's Bureau)ViiV Healthcare (Advisor or Review Panel member, Speaker's Bureau) Moti Rampogal, MD, Gilead Sciences (Consultant, Research Grant or Support, Speaker's Bureau)Janssen (Consultant, Research Grant or Support, Speaker's Bureau)Merck (Consultant, Research Grant or Support)ViiV Healthcare (Consultant, Research Grant or Support, Speaker's Bureau) Keith Henry, MD, Gilead (Research Grant or Support, Paid to institution)GSK/ViiV (Research Grant or Support, Paid to institution)Janssen (Research Grant or Support, Paid to institution)Merck (Research Grant or Support, Paid to institution) Hailin Huang, PhD, Gilead Sciences Inc. (Employee, Shareholder) Kristen Andreatta, MSc, Gilead Sciences (Employee, Shareholder) Hal Martin, MD, MPH, Gilead Sciences Inc. (Employee, Shareholder)